GLUT3 as an Intersection of Glycerophospholipid Metabolism and the Innate Immune Response to Candida albicans - Wu, Xian; Zhang, Ge; Yang, Wen-Hang; Cui, Jing-Tao; Zhang, Li; Xiao, Meng; Xu, Ying-Chun (Frontiers in Cellular and Infection Microbiology, 2021)
As innate immune cells, monocytes play a central role in antifungal immunity. However, cellular metabolic events concerned with regulation of immune function during infection have not been elucidated. Using proteome and metabolome studies in primary human monocytes, we show that stimulation of monocytes by Candida albicans was accompanied by upregulation of glucose transporter 3 (GLUT3) and activation of glycerophospholipid metabolism pathway. Upregulated GLUT3 expression was initially validated in monocytes from candidemia patients. Our results also demonstrate that the innate immune responses against C. albicans are energy-dependent processes. In the early stage of infection, the conversion of intracellular metabolite pathways which act to maintain survival and limit innate immune function. In summary, our findings indicate the importance of GLUT3 in the complex network of glycerophospholipid metabolism and innate immune response triggered by C. albicans and reveal potential therapeutic targets for treatment of candidemia.